An Analysis of Contemporary Sources to Uncover the Medieval Identity of the Drink Bochet - Susan Verberg (EXARC Journal)
When Le Ménagier de Paris (1393), a medieval household manual detailing a woman's proper behavior in marriage and running a household, was newly translated and republished as The Good Wife’s Guide: a Medieval Household Book by the Cornell University Press in 2009, its collection of recipes – including one for bochet – became easily available to the general public. As the word bochet is not connected to a modern definition, the original French name for a recipe using caramelized honey was retained, and the word bochet began to signify the product of this one recipe: a mead made with caramelized honey. The homebrewing community embraced this bochet, and the resulting burnt-honey mead style has gathered enthusiastic followers. The renewed interest by the general public in the medieval period– whether truly medieval or not – is reflected in a practice whereby commercial craft brewers use neomedieval symbolism to brand their products and increase their potential value.